2021
DOI: 10.1038/s41438-021-00486-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor WRKY22 regulates canker susceptibility in sweet orange (Citrus sinensis Osbeck) by enhancing cell enlargement and CsLOB1 expression

Abstract: Pathological hypertrophy (cell enlargement) plays an important role in the development of citrus canker, but its regulators are largely unknown. Although WRKY22 is known to be involved in pathogen-triggered immunity and positively regulates resistance to bacterial pathogens in Arabidopsis, rice and pepper, the CRISPR/Cas9-mediated partial knockout of CsWRKY22 improves resistance to Xanthomonas citri subsp. citri (Xcc) in Wanjincheng orange (Citrus sinensis Osbeck). Here, we demonstrate that CsWRKY22 is a nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 60 publications
2
23
0
1
Order By: Relevance
“…These two studies point to the involvement of SA levels and CsWRKY22 expression. In fact, these results corroborate our observation that plants overexpressing CsSAMT somehow repress CsWRKY22 and are more resistant to citrus canker disease ( Wang et al, 2019 ; Long et al, 2021 ). Curiously, the presence of the pathogen (T24) led to a decrease in expression of CsPAL , CsNPR1 , and CsPR1 defense-related genes in all the plants ( Supplementary Figure 8 ), but repression was transient in the transgenic plants.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These two studies point to the involvement of SA levels and CsWRKY22 expression. In fact, these results corroborate our observation that plants overexpressing CsSAMT somehow repress CsWRKY22 and are more resistant to citrus canker disease ( Wang et al, 2019 ; Long et al, 2021 ). Curiously, the presence of the pathogen (T24) led to a decrease in expression of CsPAL , CsNPR1 , and CsPR1 defense-related genes in all the plants ( Supplementary Figure 8 ), but repression was transient in the transgenic plants.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, expression of NPR3 was higher only in VSAMT44 at T0, showing that the presence of free NPR1 monomers requires a high amount of NPR3, which is not observed in the presence of the pathogen (T24 and T48). Curiously, CsWRKY22 , a transcription factor associated with susceptibility to citrus canker and SA ( Kloth et al, 2016 ; Wang et al, 2019 ; Long et al, 2021 ), showed a significant lower expression in VSAMT44 at T0, when the pathogen was not present in the plant, suggesting that salicylic acid can modulate the expression of CsWRKY22 and consequently reflect the reduced symptoms observed in the primary infection ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CsWRKY22 , MdWRKY15 , and LiWRKY enhance the resistance of orange ( Citrus sinensis Osbeck), apple ( Malus × domestica ), and Easter lily ( Lilium longiflorum ) to Xanthomonas citri subsp. citri , Botryosphaeria dothidea , and Botrytis cinerea , respectively ( Zhao X. Y. et al, 2020 ; Kumari et al, 2021 ; Long et al, 2021 ). Heterologous expression of PtrWRKY73 in Arabidopsis ( Arabidopsis thaliana ) activates the expression of other downstream genes in the SA pathway and enhances resistance to the pathogen Pseudomonas syringae pathovar tomato strain DC3000 (Pst DC3000) ( Duan et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study on citrus fruit, CsWRKY65 and CsWRKY70 were found to be important regulators of plant resistance against P. digitatum ( Deng et al, 2020 ; Wang et al, 2021 ). And CsWRKY22 in sweet orange could promote the expression of CsLOB1 and enhance the susceptibility to canker ( Long et al, 2021 ). Thus, the isolation and cloning of citrus disease resistance WRKY TFs genes and the exploration of molecular mechanism therein are of great significance.…”
Section: Introductionmentioning
confidence: 99%